Perbedaan Karakteristik Spray Bahan Bakar Minyak Jelantah Dan Biodiesel Menggunakan Air-Assisted Nozzle Dan Cerobong Pemanasan Awal - Maulana, Fachrian Rizky; Ghurri, Ainul; Parwata, I Made (Teknik Desain Mekanika; Vol 13 No 4 (2024): Oktober 202 :4 Teknik Desain Mekanik, 2024)
Abstract Air-assisted Atomizer has an advantage in the fuel atomization process that is achieved with the help of air, and that will make good characteristics of spray. The spray characteristics are spray range and spray angle. The using of preheating funnel and preheating treatment on fuel can help the vaporization of the fuel spray, wich will increase the result of the atomization. In this research, the nozzle diameter experimental method that will be used is 2,5 mm, with using preheating funnel. The fuel that will be used are waste cooking oil and biodiesel. The results of this research showed a difference in spray characteristics between waste cooking oil and biodiesel. Waste cooking oil produces a longer spray range than biodiesel. For the result of spray angle, waste cooking oil has a slightly wider angle than biodiesel, which is only 0.06o. Keywords: Preheating, Nozzle, Air-Assisted Atomizer, Spray Characteristics